2006
DOI: 10.1203/01.pdr.0000238248.42925.f4
|View full text |Cite
|
Sign up to set email alerts
|

Protective Strategies of High-Frequency Oscillatory Ventilation in a Rabbit Model

Abstract: High-frequency oscillatory ventilation (HFOV) causes less severe lung injury than conventional mechanical ventilation (CMV) but the optimal frequency for HFOV has not been determined. We hypothesized that 15 Hz HFOV would be more protective than 5 Hz HFOV in a rabbit model of acute lung injury. Surfactant-depleted rabbits were ventilated at 15 Hz or 5 Hz HFOV for 4 h, or not ventilated, to characterize the extent of lung injury before HFOV. PaO 2 and PaCO 2 were measured throughout the experiment, and lung mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…This change in practice is likely related to evolution of our understanding of the lung protective effects of HFOV. Meyer et al (20) and Liu et al (6) used an animal model to demonstrate less lung injury and reduced levels of inflammatory mediators using a higher Hertz strategy. Hager et al (21) examined factors determining Vt during HFOV in both a test lung model and patients using a hot wire anemometer placed in series with a Sensormedics 3100B high-frequency ventilator.…”
Section: Discussionmentioning
confidence: 99%
“…This change in practice is likely related to evolution of our understanding of the lung protective effects of HFOV. Meyer et al (20) and Liu et al (6) used an animal model to demonstrate less lung injury and reduced levels of inflammatory mediators using a higher Hertz strategy. Hager et al (21) examined factors determining Vt during HFOV in both a test lung model and patients using a hot wire anemometer placed in series with a Sensormedics 3100B high-frequency ventilator.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with a previous study, which found that HFOV at higher frequencies yielded lower scores of lung injury compared with HFOV at lower frequencies in small animals. 20 The inflammatory response and the overexpression of proinflammatory mediators are contributing factors to ARDS and VILI pathogenesis. 30 We found that the levels of IL-1β and IL-6 were markedly lower in the HFOV-9 Hz group after ventilation, and the same results were obtained in different areas of the lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In pediatrics and neonatology, higher frequencies of 10-15 Hz are routinely used. One small animal study showed that in saline lavage-injured rabbits, HFOV at 15 Hz ventilation yielded lower tissue neutrophil infiltration than HFOV at 5 Hz after 4 h. 20 In adults, the recommended HFOV frequency is 5 to 6 Hz. 21 One clinical survey showed that 62.5% of adult patients with ARDS exhibited significantly improved gas exchange under HFOV.…”
Section: Critical Care Medicinementioning
confidence: 99%
“…Second, collapsed lung regions are more easily opened at higher f. 72 Third, the delivered V T is more equally distributed, as it becomes less dependent on regional compliance at higher f. 73 Lastly, the square block waveform is better preserved, allowing a more constant V T . 74,75 Needless to say, it is necessary to maintain an appropriate CDP when setting the f.…”
Section: Best Hfov Approach and Oscillator Settings For Ventilationmentioning
confidence: 99%